Conflict In Prosecuting Criminal Actions Against Someone With Digital Proof Evidence - Muhamad Jamalih (Green Publisher Indonesia, 2025)
The Criminal Law Book (abbreviated as the Criminal Code) contains instructions and descriptions regarding offenses, criminal acts, criminal acts, criminal incidents, namely regulations regarding the conditions or elements of whether or not a person can be sentenced to a crime (punishment) and rules regarding punishment, namely regulating who and how the sentence is imposed. Valid evidence in criminal case trials according to Article 184 of the Criminal Procedure Code are: Witness Statements, Expert Statements, Letters, Instructions and Defendant Statements. So the judge can use his freedom of independence to assess the strength of the evidence with a guide in certain circumstances. The formulation of the problem is in accordance with the introductory explanation above, namely: What is the legal position of the dispute over digital guidance devices referred to as CCTV in criminal trials? Why can the clue evidence referred to by CCTV influence the judge's confidence in deciding the criminal case? This study is about Normative Juridical Analysis of the existence of related digital aid complications which are used as a means of evidence in police investigations up to the court stage.